Kritik Terhadap Sekularisasi Ilmu dalam Pandangan Syed Hossen Nasr dan Korelasinya Dalam Pembangunan Ilmu Hukum Tansendental - Zulfiko, Riki (eScience Humanity Journal, 2024)
This research aims to see the view or criticism of the secularization of science from the view of an Islamic thinker from Iran named Syed Hossein Nasr and relate it to legal development in Indonesia, which uses a transcendental perspective. The development of science, which tends to be secular, is due to the separation of science from religion, especially in the Western scientific tradition, which began in the Renaissance era and resulted in the drying out of Western science from transcendental values. The two problems raised in this research are how Syed An Nashr's concept of thinking views the secularization of science and how Syed An Nashr's thinking correlates with the development of transcendental legal science in Indonesia. The result of this research is that Syed Hossein Nasr, an Islamic thinker with his Perennial philosophy, explains the importance of returning transcendental values ​​to science. Nasr's thinking also correlates with the transcendental legal perspective developed as a response to the dryness of law from the divine aspect.